PENGARUH DUKUNGAN REKAN KERJA DAN ETIKA PROFESIONAL TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK (KAP) DI JAKARTA - Maulita, Dian (Universitas Serang Raya, 2015)
This research is aimed at measuring the causal influence of a variable on performance. The data used is primary data, data collection techniques by distributing questionnaires. The sampling technique used is simple random sampling. The population in this study is the auditors who work in public accounting firms in Jakarta and sample amounted to 83 people. The experiment was conducted on 8 Kantr Public Accountants in Jakarta. Data from the results of questionnaires processed using SPSS thus obtained in the form of multiple regression equation.From the results of the t test calculation, obtained t> t table ie 10 619> 1,671 while sig.t <? 5% ie 0.000 <0.05, it can be concluded peer support variables significantly influence the performance of auditors. From the results of the t test calculation, obtained t> t table ie 8483> 1671 while sig.t <? 5% ie 0.000 <0.05, it can be concluded professional ethics variables significantly influence the performance of auditors. From the results of test calculations f, obtained Fhitung> Ftabel ie 425 890> 3:11 while sig.f <? 5% ie 0.000 <0.05, it can be concluded that there is significant influence between peer support and professional ethics on the performance of auditors. Multiple correlation Motede stated that the correlation between peer support and professional ethics on the performance of the auditor is a strong and positive relationship, which if peer support and professional ethics increases then be followed by an increase in auditor performance. Keywords: Support co-workers, professional ethics, performance.